Artefatos ou instrumentos no Métier do professor de língua inglesa da rede pública: recursos tecnológicos e o agir docente nos textos de instrução ao sósia - Riciolli, Ana Maria Barbosa Varanda [UNESP] (2015)
This work analyzed the acting of two English (LI) teachers (named S1 and S2) of municipal public Elementary schools from Joviânia (GO State). Whereby the Instruction to the Double - ID procedure (CLOT, 2007a), texts of S1 and S2 where produced in a context of use of technology, aiming at investigating which is the representation revealed in the language actions of those teachers and how they transfer that image to their pedagogical practice in English teaching. It was used computational tool AntConc to organize the analysis of the collected data. Therein, the aim of this work was to infer the dimensions of instrumental genesis from the linguistic-discursive elements found in the texts, such as instrumentation and instrumentalization, from the point of view of Socio-Discursive Interactionism (BRONCKART, 2009) and instrumental approach (RABARDEL, 1995, 2002; RABARDEL & WAERN, 2003). This approach focuses on Vygotsky's ideas, emphasizing that an instrument consists of an intermediate element which stands between psychic operations and the device. Acting over it, it is the instrument that will determine human activity. Even if a material or symbolic resource is available to a user for a given task, it will only be useful if the user knows which tasks correspond to the proposed activity and how they do it (RABARDEL, 2002). When it comes to language and the educational duty, Clot (2007a) emphasizes that the subject expresses in words their thoughts about work and in work situation. These texts are relevant for the comprehension of the teacher's action, therefore, once collected, data were selected and classified according to the theoretical and methodological frame of ALTER group, which is anchored to the Socio-Discursive Interactionism - ISD (BRONCKART, 2006, 2007, 2008, 2009; BRONKCART, MACHADO, 2004; MACHADO et al., 2009a, 2009b). From the speeches produced by the ID, it is possible to see that S1 and S2 both report, whereby their ...